Model reconstruction in adaptive machining for near-net-shape rolling compressor blades. Issue 2 (1st February 2018) - Cui, Kang; Wang, Wenhu; Jiang, Ruisong; Zhao, Dezhong
ABSTRACT: Because of its high productivity, the near-net-shape rolling process has received much attention for the manufacture of compressor blades of gas-turbine. However, due to the inherent characteristic of the rolling process, the material forced outward at the edges of the rolling blade still needs to be removed. Since each blade suffers from a different surface deformation within the tolerance zone, edges machined based on the nominal CAD model may not transition to the blade body smoothly. To solve this problem, an adaptive modelling method for machining surfaces of near-net-shape rolling blades is proposed. Through a rigid transformation and a subsequent deformation adjustment, each reference curve of the nominal CAD model can be registered to the corresponding measurement point set without losing its original shapes seriously, and then be used as the sectional curve of machining surfaces. Finally, the proposed method is verified on some blades, and the experimental results show that the edges milled with the reconstructed machining surfaces can transition to the blade body smoothly and accurately.